PERANCANGAN SISTEM PAKAR FINAL CHECK MOTOR MATIC MENGGUNAKAN METODE FORWARD CHAINING STUDI KASUS AHASS 9677 - Wahit Desta Prastowo; Kusrini Kusrini; Ferry Wahyu Wibowo (Informasi Interaktif, 2019)
The increasing interest of consumers towards motorcycle products, especially products from Honda, is now very high. The interest in purchasing Honda matic motorcycles that continues to increase is inversely proportional to the number of technicians and service centers, resulting in an imbalance between the AHASS 9677 service service and motorcycle users. This is indicated by the accumulation of queues reaching 30 units in a day so that consumers queue for hours even though only to ask questions to find out the damage and solutions and the estimated cost of damage to the vehicle owned. Technological advances can be used as an effort to retain customers and overcome queue problems that accumulate with one way of applying artificial intelligence by making an Expert System using the Forward Chaining method that can accept damage symptom input and provide damage analysis and solutions then provide estimated service costs.   Keywords: Expert System, Honda Matic Motor, Forward Chaining.